The usage of the «Rule of law» in the practice of the European Court of Human Rights and the civil procedure code of Ukraine - Кіt, Taras (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
The article is researched how is using the principle of «rule of law», based on the analysis of the practice of the European Court of Human Rights and the Civil Procedure Code of Ukraine. The understanding of the «rule of law»  is actual task, which promotes expansion of using this principle and ensuring the effective protection of human rights when are considering cases by courts of general jurisdiction.In the national scientific doctrine is using the term «rule of law»,close to the idea of English law and is built on the methodology of legal positivism. In the special study «Rule of Law Checklist» interpretation is another than positivism perception of the principle and is based on the doctrine of the natural law.Elements of the principle are listed in the control list adopted by the Venice Commission in 2016, which we analyzed with a compare the provisions of the current civil procedural legislation and the practice of the European Court.Was established that the appliance of «rule of law» is carried out at the stage of making a court decision, which legal norm is applicable to the legal relationship.The usage of the element «legality» as a component of the «rule of law» has been summarized by us as the right of the court to use the norms of the Constitution of Ukraine as norms of direct effect; the court’s obligation to use an international agreement, in case of non-compliance the legal act with the norms of the international act; when law which regulates disputed relations is absence, the court is using the law that is regulating relationships similar in content (analogy of the law), and if in the absence of such law, the court is proceeding from the general principles of legislation (analogy of law).Analysis, of provisions of national civil procedural legislation, gives grounds for concluding that there are both: legislative prerequisites and practical implementation of the «rule of law».Simultaneously we believe, that one of the legislator’s priority directions should be further improvement in the increasing access to justice. Namely to obligate the parties to use alternative dispute resolution, which will reduce the number of court proceedings.